DESIGN WAYPOINT DRONE HEXACOPTER MODEL USING SUGENO FUZZY LOGIC - Akhmad Khoirunnas; Jainur Rahman; Imam Ashar (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
Fuzzy logic is a scientific branch of Artificial Intelligence that was developed and applied to machines to be able to approach human intelligence. In order this machine or tool to be able to execute commands in a "more humane" manner, this AI uses a rule base as a reference for movement which then goes into the defuzzyication process. To apply the fuzzy logic rule base on the drone movement automatically, an error value is taken at tetta (θ) which was previously processed by the Odometery Method by taking the position value of the drone with GPS. In addition, the drone is also monitored through Android in real-time so that the user can see the position and set the goals of the drone. In order for the processor and realtime process to run optimally, the drone will use Arduino Mega as a processor, control center, and read input from each sensor related to the drone before entering FireBase (Cloud Data Base). Control of the stability of the drone system in the air is obtained by processing GPS sensors with the fuzzy logic method with an error at reading of coordinate is 0,4 meter from line distance that is given and response acceleration of fuzzy to reset the drone back to the distance of 4 m/s.